The hitman's wife's bodyguard [videorecording (Blu-Ray)] - Hughes, Patrick, 1978-; Reynolds, Ryan; Jackson, Samuel L.; Hayek, Salma, 1966- (Lionsgate, 2021)
A top protection agent must guard the life of his mortal enemy, a notorious hitman, and his wife when new danger threatens all of them.